2016
DOI: 10.1177/0883073815627880
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing in Pediatric Neurology Patients

Abstract: Genetic heterogeneity in neurologic disorders has been an obstacle to phenotype-based diagnostic testing. The authors hypothesized that information compiled via whole exome sequencing will improve clinical diagnosis and management of pediatric neurology patients. The authors performed a retrospective chart review of patients evaluated in the University of Michigan Pediatric Neurology clinic between 6/2011 and 6/2015. The authors recorded previous diagnostic testing, indications for whole exome sequencing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Successful application of WES in pediatric neurology has been confined mostly to single case reports and retrospective studies in which WES was used as a last-resource genetic test. 5 , 6 , 7 , 8 , 9 , 10 , 11 However, prospective clinical utility studies of larger groups of patients have not yet been performed. Here, we present such data for a cohort of 150 patients who received both the standard diagnostic assessment and WES, allowing a direct comparison of the performance of both trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Successful application of WES in pediatric neurology has been confined mostly to single case reports and retrospective studies in which WES was used as a last-resource genetic test. 5 , 6 , 7 , 8 , 9 , 10 , 11 However, prospective clinical utility studies of larger groups of patients have not yet been performed. Here, we present such data for a cohort of 150 patients who received both the standard diagnostic assessment and WES, allowing a direct comparison of the performance of both trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the cost of comprehensive genetic testing such as whole exome and genome sequencing (WES/WGS) has decreased enough to make it a cost-effective tool in the diagnosis of individuals with suspected genetic conditions (Nolan & Carlson, 2016;Stark et al, 2017). Through use of this technology, patients and families who have been searching for answers for years are finally given an explanation (Lee et al, 2014;de Ligt et al, 2012;Sawyer et al, 2016;Shashi et al, 2014;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper estimated that with the use of WES there is the potential for an estimated average savings of $2465.62 and $502.52 (the average charge estimate on secondary genetic and metabolic testing, respectively) and up to $13,305.00 and $2340.00 (the maximum charge estimate on secondary genetic and metabolic testing, respectively). It is suggested that WES charge could be lower than the composite required for more conventional secondary genetic and metabolic laboratory testing [ 12 ]. Limiting the molecular screening to the Mendeliome, which comprehends the genes that are known to cause a Mendelian disorder, WES appears a highly informative and convenient first-tier tool in the diagnostic setting.…”
Section: Discussionmentioning
confidence: 99%